A pilot study investigating cortical haemodynamic and physiological correlates of exercise cognition in trained and untrained cyclists over an incremental self-paced performance test, while thinking aloud. (May 2021) - Robinson, Nicola J.; Montgomery, Catharine; Swettenham, Laura; Whitehead, Amy
Abstract: Objectives: Few studies have directly investigated changes in cortical haemodynamics during a self-paced interval endurance activity, while collecting conscious cognition and physiological performance data. This pilot study used functional Near Infrared Spectroscopy (fNIRS), while capturing conscious cognition using Think Aloud (TA) during an incremental paced cycling exercise. Methods: A mixed design was implemented with cycling expertise (untrained vs. trained) as the between groups variable and incremental self-paced stage (5 stages of increasing effort) and site (12 optodes across the PFC) as the within groups variables. Dependent measures were the changes in cortical O2 Hb, and physiological indicators (% heart rate max (%HRmax), average power output (APO), peak power output (PPO), rate of perceived exertion (RPE) and blood lactate (Bla)) over time. Participants used TA throughout their second interval trial. Results: Trained cyclists had higher APO and maximum power output (MPO) from stages 2–5, in addition to a greater increase in PPO over the whole trial. There were significant main effects of stage on %HRmax, Bla and RPE. Differences in cortical haemodynamics were found specifically in areas in the mid left and right PFC. TA data demonstrated that untrained participants verbalised more irrelevant information and feelings of pain and fatigue, in addition to both groups verbalising significantly more motivation-related thoughts during the final stage. Conclusion: This pilot is the first to capture changes in Cox, physiological measures and conscious cognition through the use of TA. We demonstrate the potential role of mid- PFC, and how conscious cognition may change over time. This study has implications for coaches and sport psychologists who may want to understand the cognitions of their athlete during an event and support low level athletes in developing a better understanding of the own cognitions. Highlights: Differences in Cox between trained and untrained participants were found, specifically in the Left DLPFC. Untrained participants verbalised more irrelevant information and feelings of pain and fatigue. Both trained and untrained participants verbalised more motivational related thoughts during the final stage of the trial. As oxygen utilisation increased in the left DLPFC, both trained and untrained participants use more motivational self-talk. This is the first study to consider Cox, physiological measures and conscious cognition during an incremental cycling test.